PENINGKATAN HASIL BELAJAR TEMA 8 MELALUI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) BERBANTUAN MEDIA TEKA-TEKI SILANG DI KELAS V SDN WIRUN - Diah Evi Yuliastanti Diah; Wawan Shokib Rondli; Gunawan Setiadi (STKIP Subang, 2023)
This study aims to determine the increase in learning outcomes in theme 8 through the Numbered Head Together (NHT) learning model assisted by crosswords in class V SDN Wirun. The research method used was classroom action research (PTK) conducted in 2 cycles. The research design is based on planning, action, observation, and reflection. Data obtained through documentation techniques, interviews, observations, and tests. The results showed that the Numbered Head Together (NHT) learning model assisted by crosswords media could improve student learning outcomes with the average class I cycle PPKn content reaching 70.62 while the IPS content reached 65.37. Then the learning outcomes of students in cycle II increased with the average learning outcomes for PPKn content reaching 82.37 while the IPS content reached 79.87. Based on the results of the study, it can be concluded that the application of the Numbered Head Together (NHT) learning model assisted by crosswords media is able to improve the learning outcomes of class V SDN Wirun on PPKn and Social Studies content.